COMPARATIVE STUDY ON THE PHYTOCHEMICAL CONTENT OF THE SEEDS AND FRUITS OF THREE CUCURBITS (FULafia Journal of Science and Technology, 2017)
A comparative study was carried out on the phytochemical cotent of the seeds and fruits of Cucumis melo (L.), Lagenaria  reviflora(Benth) and Citrullus lanatus(Thunb). Phytochemical analysis of air-dried, powdered epicarp, mesocarp and seeds of the mature fruits were carried out using standard procedures. Data on phytochemical characteristics were collected and subjected to two - way analysis of variance (ANOVA) at p